Opportunities and challenges in the use of educational apps as a support tool in the development process of people with Autism Spectrum Disorder (ASD) - Vega, Alexandre Pereira; Laffront, Rodrigo; Cardoso, Cristina Luz (Anais do Simpósio Brasileiro de Jogos e Entretenimento Digital (SBGames), 2024)
The use of mobile applications and games as educational tools for people with Autism Spectrum Disorder (ASD) assists in the learning process and in the development of skills. This article presents two case studies involving institutions that offer support for people with ASD. Through literature reviews, interviews and observations, teachers' experiences regarding the use of mobile applications as support tools were verified. It was possible to observe that the educators interviewed are adapted to the use of technology in the classroom but recommend controlling time to avoid excessive use. The challenges and methods for implementing the activities, guidance and encouragement for the use of applications, the sharing strategy and distractions are also discussed.